2023
DOI: 10.1186/s12891-023-06592-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a course of selected corrective exercises on posture, scapula-humeral rhythm and performance of adolescent volleyball players with upper cross syndrome

Abstract: Background This study aims to investigate the effect of a course of selected corrective exercises on posture, scapula-humeral rhythm and performance of adolescent volleyball players. Methods 30 adolescent volleyball players with upper cross syndrome were purposefully selected and assigned into 2 control and training groups. The degree of back curvature was evaluated using a flexible ruler, forward head and forward shoulder size by photographic meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Corrective exercises could be an effective method in reducing shoulder girdle and spine abnormalities, thus improving the performance of volleyball players. This was confirmed by Firouzjah et al (43) who concluded that execution of correction exercises for 10 weeks (three sessions per week with a duration of each session 30-70 minutes) was an effective tool in shoulder girdle and spine abnormality reduction, thus improving performance in adolescent volleyball players with the upper cross syndrome. The D arm's submaximal force repetition error of the ER was smaller than in the ND arm (4 N in the D shoulder and 5 N in the ND shoulder) and in the extensor muscles (5 N in the D arm and 7 N in the ND arm), but this was not determined for IR muscles (5 N in both shoulders).…”
Section: Discussionmentioning
confidence: 65%
“…Corrective exercises could be an effective method in reducing shoulder girdle and spine abnormalities, thus improving the performance of volleyball players. This was confirmed by Firouzjah et al (43) who concluded that execution of correction exercises for 10 weeks (three sessions per week with a duration of each session 30-70 minutes) was an effective tool in shoulder girdle and spine abnormality reduction, thus improving performance in adolescent volleyball players with the upper cross syndrome. The D arm's submaximal force repetition error of the ER was smaller than in the ND arm (4 N in the D shoulder and 5 N in the ND shoulder) and in the extensor muscles (5 N in the D arm and 7 N in the ND arm), but this was not determined for IR muscles (5 N in both shoulders).…”
Section: Discussionmentioning
confidence: 65%
“…Eighteen studies have examined the effect of therapeutic exercise on thoracic kyphosis [ 10 13 , 17 , 18 , 22 – 30 , 33 , 35 , 36 ]. In three studies, both independent intervention groups were utilized, while in one study, all three independent intervention groups were included.…”
Section: Resultsmentioning
confidence: 99%
“… Guo et al, 2023 [ 31 ] College students Intervention group: 20 (11/9)( 19.00 ± 0.97) Control group: 20(7/13)( 18.85 ± 0.88) cervical and thoracic “Daoyin” training. No Exercise (8), (5), (NA) Forward Head, Forward Shoulder obvious improvement in the forward head angle, forward shoulder angle, Park et al, 2014 [ 32 ] children Intervention group: 20 (10/10)( 13.55 ± 2.21) Control group: 20(10/10)( 13.75 ± 1.80 Strengthening and stretching exercise No Exercise (25), (3), (NA) Forward Head, Forward Shoulder The complex training improved posture Firouzjah et al, 2023 [ 33 ] volleyball players Intervention group: 15 ( 16/46 ± 0/63) Control group: 15 ( 16/80 ± 0/77) Strengthening and stretching exercise No Exercise (10), (3), (30–70) Forward Head, Forward Shoulder, Kyphosis significant good effect on forward head, forward shoulder, and kyphosis. Ruivo et al, 2016 [ 34 ] adolescents Intervention group: 42(16/26) (15.5 ± 1.0) Control group: 46(15/31) (15.9 ± 1.1) Strengthening and stretching exercise in addition to Physical Education classes Physical Education classes (32), (2), (NA) Forward Head, Forward Shoulder The exercise intervention successfully decreased the forward head and protracted shoulder in adolescents.…”
Section: Methodsmentioning
confidence: 99%